COVID-19 and livable cities in Asia and the Pacific guidance note. (Asian Development Bank, 2020)
COVID-19 is causing an unprecedented global impact on cities across the world. The proposed approaches and actions discussed in this guidance note are anchored to the core principles of ADB Strategy 2030 Operational Plan for Priority 4: Making Cities More Livable and also considers the public health and economic impacts of the pandemic. The guidance note is one of a series produced by ADB for key sectors and thematic areas.